Sequential simulation of regeneration-specific microenvironments using scaffolds loaded with nanoplatelet vesicles enhances bone regeneration - Wenshuai Li; Qichen Shen; Tong Tong; Hongsen Tian; Xiaowei Lian; Haoli Wang; Ke Yang; Zhanqiu Dai; Yijun Li; Xianhua Chen; Qingqing Wang; Dan Yang; et al. (Bioactive Materials)
Bone regeneration is a complex and coordinated physiological process, and the different stages of this process have corresponding microenvironments to support cell development and physiological activities. However, biological scaffolds that provide different three-dimensional environments during different stages of bone regeneration are lacking. In this study, we report a novel composite scaffold (NPE@DCBM) inspired by the stages of bone regeneration; this scaffold was composed of a fibrin hydrogel loaded with nanoplatelet vesicles (NPVs), designated as NPE, and decellularized cancellous bone matrix (DCBM) microparticles. Initially, the NPE rapidly established a temporary microenvironment conducive to cell migration and angiogenesis. Subsequently, the DCBM simulated the molecular structure of bone and promoted new bone formation. In vitro, the NPVs regulated lipid metabolism in bone marrow mesenchymal stem cells (BMSCs), reprogramed the fate of BMSCs by activating the PI3K/AKT and MAPK/ERK positive feedback pathways, and increased BMSC functions, including proliferation, migration and proangiogenic potential. In vivo, NPV@DCBM accelerated bone tissue regeneration and repair. Initially, the NPE rapidly induced angiogenesis between DCBM microparticles, and subsequently, BMSCs differentiated into osteoblasts with DCBM microparticles at their core. In summary, the design of this composite scaffold that sequentially mimics different bone regeneration microenvironments may provide a promising strategy for bone regeneration, with clinical translational potential.